FRI0271 Modular Analysis of Peripheral Blood Gene Expression in Rheumatoid Arthritis Captures Reproducible Gene Expression Changes in TNF Responders. (10th June 2014) - Curran, M.; Oswald, M.; Lee, A.; Cherkas, Y.; Brodmerkel, C.; Lamberth, S.; Gregersen, P.K.
Abstract : Background: The use of whole blood gene expression to predict and follow the response to TNF inhibition therapy in RA has been challenging due to the complex nature of the data. Objectives: Here we employ an approach to gene expression analysis that is based on gene expression "modules" previously reported by Chaussabel, et al. (1) Methods: Whole blood RNA (PAXgene) was obtained at baseline and 12 weeks on two cohorts of rheumatoid arthritis patients beginning anti-TNF therapy. The initial cohort was enrolled by the Autoimmune Biomarkers Collaborative Network (ABCoN) and contains 50 subjects stratified by EULAR Good Responders (N=14), Moderate Responders (N=21) and Non Responders (N=15) at 12 weeks after starting therapy. Results: Good and Moderate Responders exhibited highly significant changes in multiple modules using a hypergeometric analysis. These included dramatic decreases in modules related to the myeloid lineage and inflammation, along with increases in B cell and plasma cell modules as well as in a number of modules related to the MHC and ribosomal proteins and other "undefined" module groups. Strikingly, Non Responders exhibited very little change in any modules. We have replicated these data in patients enrolled in a clinical trial of Simponi®, with full expression data available on 29 Good Responders, and 37 Moderate Responders. We observed nearly identical modular changes to those identified in the ABCoN Responders after 14 weeks of treatment. Only 6 Non Responders were available for study in this dataset, making convincing replication difficult for this subgroup. Several other replication datasets are currently being analyzed. Conclusions: These data suggest that using gene expression modules related to inflammatory disease may provide a valuable method of characterizing the responder status of RA patients treated with TNF inhibitors. References: Chaussabel D, Quinn C, Shen J, Patel P, Glaser C, Baldwin N, Stichweh D, Blankenship D, Li L, Munagala I, Bennett L, Allantaz F, Mejias A, Ardura M, Kaizer E, Monnet L, Allman W, Randall H, Johnson D, Lanier A, Punaro M, Wittkowski KM, White P, Fay J, Klintmalm G, Ramilo O, Palucka AK, Banchereau J, Pascual V. A modular analysis framework for blood genomics studies: application to systemic lupus erythematosus. Immunity. 2008 Jul 18;29(1):150-64. doi: 10.1016/j.immuni.2008.05.012. Disclosure of Interest: M. Curran Employee of: Janssen Research & Development, LLC., M. Oswald Grant/research support: Janssen Research & Development, LLC., A. Lee Grant/research support: Janssen Research & Development, LLC., Y. Cherkas Employee of: Janssen Research & Development, LLC., C. Brodmerkel Employee of: Janssen Research & Development, LLC., S. Lamberth Employee of: Janssen Research & Development, LLC., P. Gregersen Grant/research support: Janssen Research & Development, LLC. DOI: 10.1136/annrheumdis-2014-eular.3724